Early Intervention for LGBTQ Health: A 10-Hour Curriculum for Preclinical Health Professions Students - Minturn, Matthew S. (MedEdPORTAL, 2021)
INTRODUCTION: Individuals who identify as lesbian, gay, bisexual, transgender, or queer (LGBTQ) face significant health disparities and barriers to accessing care. Patients have reported provider lack of knowledge as one of the key barriers to culturally responsive, clinically competent care. Many US and Canadian medical schools still offer few curricular hours dedicated to LGBTQ-related topics, and medical students continue to feel unprepared to care for LGBTQ patients. METHODS: We developed a 10-hour LGBTQ health curriculum for preclinical medical and physician assistant students. The curriculum included lectures and case-based small-group discussions covering LGBTQ terminology, inclusive sexual history taking, primary care and health maintenance, and transition-related care. It also included a panel discussion with LGBTQ community members and a small-group practice session with standardized patients. Students were surveyed before and after completing the curriculum to assess for increases in confidence and knowledge related to LGBTQ-specific care. RESULTS: Forty first- and second-year medical students completed the sessions and provided valid responses on pre- and postcourse surveys. Nearly all students initially felt unprepared to sensitively elicit information, summarize special health needs and primary care recommendations, and identify community resources for LGBTQ individuals. There was significant improvement in students' confidence in meeting these objectives after completion of the five sessions. Knowledge of LGBTQ health issues increased minimally, but there was a significant increase in knowledge of LGBTQ-related terminology. DISCUSSION: Our 10-hour LGBTQ health curriculum was effective at improving medical students' self-confidence in working with LGBTQ patients but was less effective at increasing LGBTQ-related medical knowledge.